2011
DOI: 10.1051/epjconf/20111715001
|View full text |Cite
|
Sign up to set email alerts
|

Fusion11 Conference Summary

Abstract: Abstract. A summary account of the conference "Fusion11", held in Saint Malo, France, May 2-6, 2011.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In recent years, many efforts have been made to understand the effect of breakup of weakly bound nuclei during the fusion reaction in very asymmetric reactions where the capture cross section is equal to the complete fusion cross section [2,[44][45][46][47][48][49][50]. The light radioactive nuclei, especially halo nuclei, such as 6 He, 8 B, 11 Be, and the stable nuclei 6 Li and 9 Be are weakly bounded, hence there is a chance of the breakup in the colliding process.…”
Section: Reactions With Weakly Bound Projectiles At Energies Around Cmentioning
confidence: 99%
“…In recent years, many efforts have been made to understand the effect of breakup of weakly bound nuclei during the fusion reaction in very asymmetric reactions where the capture cross section is equal to the complete fusion cross section [2,[44][45][46][47][48][49][50]. The light radioactive nuclei, especially halo nuclei, such as 6 He, 8 B, 11 Be, and the stable nuclei 6 Li and 9 Be are weakly bounded, hence there is a chance of the breakup in the colliding process.…”
Section: Reactions With Weakly Bound Projectiles At Energies Around Cmentioning
confidence: 99%
“…In recent years, many efforts have been made to understand the effect of breakup of weakly bound nuclei during the fusion reaction in very asymmetric reactions where the capture cross section is equal to the complete fusion cross section [1][2][3][4][5][6][7][8][9]. The light radioactive nuclei, especially halo nuclei, such as 6 He, 8 B, 11 Be, and the stable nuclei 6,7 Li and 9 Be are weakly bounded, hence there is a chance of the breakup in the colliding process.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments with various medium-light and heavy nuclei have shown that the experimental slopes of the complete fusion excitation function keep increasing at low sub-barrier energies and may become much larger than the predictions of standard coupled-channel calculations. This was identified as the fusion hindrance with the threshold energy E s [1][2][3]. More experimental and theoretical studies of sub-barrier fusion hindrance are required to improve our understanding of its physical reason, which may be especially important in astrophysical fusion reactions [4].…”
mentioning
confidence: 99%